Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au-I/Au-III catalysis: discovery of a pyridinium-oxazole dyad as an ionic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie-International Edition, 2017)
Oxidative intramolecular 1,2-amino-oxygenation reactions, combining gold(I)/gold(III) catalysis, is reported. The reaction provides efficient access to a structurally unique ionic pyridinium-oxazole dyad with tunable emission wavelengths. The application of these fluorophores as potential biomarkers has been investigated.